Current Account Deficit Sustainability: A Panel Approach - Evan, Lau; Ahmad Zubaidi, Baharumshah; Stilianos, Fountas (Center for International Economics, Sejong Institution, 2005)
Abstract In this paper we attempt to examine the issue of sustainability of current account imbalances in eight East Asia countries using the latest developments in nonstationary panel data analysis. The methods of nonstationary time series panels provide a much more promising explanation than would an analysis based on pure time series or cross section data. The empirical results clearly indicate that the current account imbalances were not on the long-run steady state in the pre-crisis era (1970-1997). This leads to the conclusion that the current accounts of Asia-8 during this period were unstable and did not move towards external account equilibrium. However, strong comovements between exports and imports are found in the extended sample period that includes the post-crisis period (1970-2000). This result implies that large currency depreciations and the economic recovery have brought the Asia-8 economies back on a sustainable path. Thus, current account imbalances may be used as an indicator (or warning signal) in predicting future crises.